3.7k views
3 votes
Type the correct answer in each box. Use numerals instead of words. Please Help!

Type the correct answer in each box. Use numerals instead of words. Please Help!-example-1
User Pbalaga
by
5.3k points

1 Answer

5 votes

Answer:

x = -3h

x = -12

Explanation:

Given expression is,


(x)/(h)+1=-2

By adding 2 on both the sides of the equation,


(x)/(h)+1+2=-2+2


(x)/(h)+3=0

Now subtract 3 form both the sides,


(x)/(h)+3-3=0-3


(x)/(h)=-3

Multiply the equation by 'h'

x = -3h

If h = 4,

By substituting h = 4 in the equation,

x = -3(4)

x = -12

User Bassirou
by
4.8k points